2013
DOI: 10.1016/j.chembiol.2013.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Telomere Length by G-Quadruplex Telomere DNA- and TERRA-Binding Protein TLS/FUS

Abstract: Mammalian telomeres comprise noncoding TTAGGG repeats in double-stranded regions with a single-stranded TTAGGG repeat 3' overhang and are bound by a multiprotein complex with a telomeric repeat-containing RNA (TERRA) containing a UUAGGG repeat as a G-quadruplex noncoding RNA. TLS/FUS is a human telomere-binding protein that was first identified as an oncogenic fusion protein in human myxoid and round-cell liposarcoma. Here, we show that the Arg-Gly-Gly domain in the C-terminal region of TLS forms a ternary com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
187
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(195 citation statements)
references
References 46 publications
6
187
0
1
Order By: Relevance
“…Some of these hybrid-binding proteins, such as nucleolin (Gonzá-lez et al 2009;Haeusler et al 2014) and FUS (Takahama et al 2013), were found in other studies to bind G-quadruplexes, which also are in non-B DNA conformations. However, not all proteins that bind G-quadruplexes bind RNA/DNA hybrids.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these hybrid-binding proteins, such as nucleolin (Gonzá-lez et al 2009;Haeusler et al 2014) and FUS (Takahama et al 2013), were found in other studies to bind G-quadruplexes, which also are in non-B DNA conformations. However, not all proteins that bind G-quadruplexes bind RNA/DNA hybrids.…”
Section: Resultsmentioning
confidence: 99%
“…TERRA can interact with telomeric DNA to form hybrid DNA-RNA G-quadruplexes, interact with components of the shelterin complex, and bind telomerase [58]. TERRA is also thought to play a role in organising and expanding telomeric heterochromatin [69] and to help in telomere homeostasis. Indeed, TERRA appears to be expressed at a higher rate from short telomeres, to nucleate enzyme clusters by binding to multiple telomerase copies, and to recruit them to its telomere of origin [67].…”
Section: Magnesium and Telomeresmentioning
confidence: 99%
“…Due to structural similarities between DNA and RNA G-quadruplexes, their binding proteins overlap significantly. Among the G-quadruplex-binding proteins are nucleolin, hnRNP, serin/arginine-rich splicing factor (SRSF) 1 and 9, splicing factor U2AF, ribosomal proteins [69], as well as TLS [51], TRF2 [53], FRM2 [65,66], and the RNA helicase associated with AU-rich element (RHAU) proteins [70]. Telomeres have been considered to be transcriptionally silent, but recently it was demonstrated that telomeres are transcribed into telomeric repeat-containing RNA (TERRA) [125].…”
Section: Proteins Involved In Interactions With Quadruplex Dnamentioning
confidence: 99%